Reliability and validity of the Japanese version of the simplified nutritional appetite questionnaire in community‐dwelling older adults. Issue 12 (16th December 2014) - Nakatsu, Nobuyuki; Sawa, Ryuichi; Misu, Shogo; Ueda, Yuya; Ono, Rei
Abstract : Aim: To translate the Simplified Nutritional Appetite Questionnaire (SNAQ) into Japanese, and assess its reliability and validity in Japanese community‐dwelling older adults. Methods: A total of 84 community‐dwelling older adults people aged 65 years or older were included in the present study, and those with a Mini‐Mental State Examination score of <24, had dementia, had digestive disease or who did not complete the examination were excluded. The SNAQ was translated into Japanese according to an internationally accepted methodology. The internal reliability of the SNAQ was evaluated by Cronbach's alpha coefficient. Test–retest reliability was evaluated using the intraclass correlation coefficient. The dimensionality of the SNAQ was evaluated by factor analysis. Concurrent validity was evaluated by measuring the Pearson's correlation coefficient between the SNAQ and Mini‐Nutritional Assessment Short‐Form scores, Geriatric Depression Scale scores, walking speed test, chair‐stand test, hand grip strength test, or the Timed Up and Go test. Results: The mean score of the Japanese version of the SNAQ was 15.5, with a Cronbach's alpha coefficient of 0.545 and intraclass correlation coefficient of 0.754. Factor analysis showed a single factor with 50.0% explained variance. The SNAQ was significantly associated with the Mini‐Nutritional Assessment Short‐Form, Geriatric Depression Scale, walking speed test, chair‐stand test and the Timed Up and Go test. Handgrip strength test did not show a significant association with the SNAQ. Conclusion: The Japanese version of the SNAQ had sufficient reliability and validity. Furthermore, SNAQ (Japanese version) is useful for evaluating the appetite of community‐dwelling older adults in Japan.Geriatr Gerontol Int 2015; 15: 1264–1269.